Effect of transplantation media on Pocillopora coral growth rate at TWAL Pulau Weh - Adrian Damora; Zulkarnain Jalil; Nanda Muhammad Razi; Muhammad Agustiar; Puad Batari Harahap; Nurul Najmi; Samsul Bahri; Munandar Munandar; Shan-Yin Vanson Liu; Chitra Octavina; Maria Ulfah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Coral reef ecosystems have a vital role in waters so that damage to coral reef ecosystems can reduce ecological and socio-economic functions that can impact environmental imbalances, such as reef fish and benthic communities. This study aims to determine the effect of transplant media on the growth rate of the genus Pocillopora coral and see whether it has a significant effect on the rate of coral growth in TWAL Pulau Weh, Aceh Province. The method used is a purposive sampling method in determining stations, analysis using the ImageJ 1.52 application. The results showed that the effect of transplant media on the growth rate of Pocillopora corals were significant differences between structures given an electric current and those not given an electric current with a 95% confidence interval. The average growth value of Pocillopora corals given an electric current is 25.06 mm/month. While the Pocillopora corals that were not given an electric current average growth value was 16.50 mm/month.Keywords:Coral reefCoral transplantElectrical stimulationPocilloporaImagej